2018
DOI: 10.1109/jstsp.2018.2855046
|View full text |Cite
|
Sign up to set email alerts
|

Zero-Delay Rate Distortion via Filtering for Vector-Valued Gaussian Sources

Abstract: We deal with zero-delay source coding of a vector-valued Gauss-Markov source subject to a mean-squared error (MSE) fidelity criterion characterized by the operational zero-delay vector-valued Gaussian rate distortion function (RDF). We address this problem by considering the nonanticipative RDF (NRDF) which is a lower bound to the causal optimal performance theoretically attainable (OPTA) function (or simply causal RDF) and operational zero-delay RDF. We recall the realization that corresponds to the optimal "… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
68
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(70 citation statements)
references
References 39 publications
2
68
0
Order By: Relevance
“…Then X and U are conditionally independent given U . Using this fact and the uniform Lipschitz property (20), we have for…”
Section: Upper Bounds On the Sequential Rate-distortion Functionmentioning
confidence: 98%
See 1 more Smart Citation
“…Then X and U are conditionally independent given U . Using this fact and the uniform Lipschitz property (20), we have for…”
Section: Upper Bounds On the Sequential Rate-distortion Functionmentioning
confidence: 98%
“…The problem becomes more intricate when causality constraints are imposed, and decisions must be made in real time. There are many recent works on this topic dealing with various types of information constraints and structural assumptions about the source (see, e.g., [13]- [20]).…”
Section: Introductionmentioning
confidence: 99%
“…All these scenarios may operate under strict requirements on latency and reliability. Particularly, delays play a critical role in the performance or stability of these systems [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the authors of [ 12 ] showed in the symmetric case, i.e., equal rates and distortions for each individual description, that the MD region for a colored Gaussian source subject to MSE distortion constraints can be achieved by predictive coding using filtering. However, similar to single-description source coding [ 8 ], the MD source coders whose performance is close to the fundamental rate-distortion bounds impose long delays on the end-to-end processing of information, i.e., the total delay only due to source coding [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation